PENGELOLAAN PELATIHAN KEJURUAN TEKNOLOGI INFORMASI KOMPUTER (TIK) PADA BALAI LATIHAN KERJA (BLK) PROVINSI BENGKULU - Haris Dwi Putra; Ilham Adbullah; Parlan Parlan (Jurnal Pendidikan Sepanjang Hayat, 2019)
The porpose of this study is to know the implementation training and evaluation on training technologies computer (TIK) at Balai Latihan Kerja (BLK) Bengkulu Province. And this method of this research used by kualitatif with interview, observasion, and documentation. The subjects were chose are employers of (BLK) that subject. On the research are Aripan Senarun, S.Sos, As Kasubbag TU, Subur, S.Sos. As chief of vocational Dwi, S.Sos, as training instruktur and than Adetia Merdanti, as learning. To prove the validity of the data. Has been chaked by using, trianggulation source, technique and time. The data analized throught three stoges are reduction, persentation, and also conclusion. From this research has been finding three fact. Firstly, Planning of training BLK Bengkulu Province, can help make and promote training programs, formulation the training, recrutment training participant, determine the curriculum, choses methods, recrutment instructor, prepare infrastructure, and also. Prepare evaluation training tols. Secondly, Implementation of training BLK Bengkulu Province, Implementation BLK using find from APBD and APBN. The curriculum that used from the government. Thirdly, Evaluation of training BLK Bengkulu Province, In the evaluation proces carried out the training organized BLK both directly and in directly.  Evaluation was also carried out on institutions, instructors, and trainees, who were used as evaluation material.                 Key Words: Management, Training, Training Center, (Balai Latihan Kerja Bengkulu).